Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1074/jbc.m604323200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Phospholipase C-γ1with Villin Regulates Epithelial Cell Migration

Abstract: Tyrosine-phosphorylated villin regulates actin dynamics, cell morphology, and cell migration. Previously, we identified four tyrosine phosphorylation sites in the amino-terminal domain of villin. In this study we report six new sites in the carboxyl-terminal region of the villin core. With this study we document all phosphorylatable tyrosine residues in villin and map them to functions of villin. In this study, we identify for the first time the functional relevance of the carboxyl-terminal domains of the vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(78 citation statements)
references
References 48 publications
4
74
0
Order By: Relevance
“…18 We have previously identified 10 phosphorylation sites in villin and demonstrated that mutation of these sites inhibits the actin severing activity of villin. 19 Further, we have demonstrated the absolute requirement of c-Src kinase for tyrosine phosphorylation of villin. 20 Gelsolin is also tyrosinephosphorylated by c-Src kinase, although the tyrosinephosphorylated residues and the significance of phosphorylation for the actin-regulatory functions of gelsolin have not been identified.…”
Section: Villin Inhibits Apoptosis By Preserving Actin Dynamicsmentioning
confidence: 73%
“…18 We have previously identified 10 phosphorylation sites in villin and demonstrated that mutation of these sites inhibits the actin severing activity of villin. 19 Further, we have demonstrated the absolute requirement of c-Src kinase for tyrosine phosphorylation of villin. 20 Gelsolin is also tyrosinephosphorylated by c-Src kinase, although the tyrosinephosphorylated residues and the significance of phosphorylation for the actin-regulatory functions of gelsolin have not been identified.…”
Section: Villin Inhibits Apoptosis By Preserving Actin Dynamicsmentioning
confidence: 73%
“…MDCK or HeLa Tet-Off cells were stably transfected with HA-tagged wild-type villin protein as described previously (16). To repress the expression of villin gene, cells were cultured in the presence of 10 ng/ml doxycycline.…”
Section: Methodsmentioning
confidence: 99%
“…To repress the expression of villin gene, cells were cultured in the presence of 10 ng/ml doxycycline. We have previously demonstrated the induction of villin following doxycycline withdrawal and shown the absence of villin in the MDCK and HeLa Tet-Off cells in the presence of doxycycline (16,17). In addition, IEC-6 cells were infected with recombinant adenovirus expressing full-length human villin protein as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations